1978
DOI: 10.1073/pnas.75.7.3050
|View full text |Cite
|
Sign up to set email alerts
|

ADP-ribosylation of membrane proteins catalyzed by cholera toxin: basis of the activation of adenylate cyclase.

Abstract: In the presence of ATP and a cytosolic factor, cholera toxin fragment A1 catalyzes the transfer of ADP-ribose from NAD to a number of soluble and membrane-bound proteins of the pigeon erythrocyte. Evidence is presented that suggests that the most readily modified membrane protein (M, 42,000 The activation of adenylate cyclase [ATP pyrophosphate-lyase (cyclizing), EC 4.6.1.1.] by cholera toxin involves the interaction of some part of the cyclase system exposed on the inner surface of the plasma membrane with NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
305
2
1

Year Published

1979
1979
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 669 publications
(314 citation statements)
references
References 15 publications
6
305
2
1
Order By: Relevance
“…Using similar conditions with [c~-32P] NAD +, we observed that cytosolic proteins were labelled in addition to plasma membrane proteins (not shown). This was in line with [6]; however, it was difficult to wash out pancreatic plasma membranes of all cytosolic components. Such difficulties have been avoided by replacing the whole erythrocyte cytosol either by a protein cofactor purified 1000-fold from this cytosol [18] or by an acetate or phosphate buffer used at high concentration [8].…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Using similar conditions with [c~-32P] NAD +, we observed that cytosolic proteins were labelled in addition to plasma membrane proteins (not shown). This was in line with [6]; however, it was difficult to wash out pancreatic plasma membranes of all cytosolic components. Such difficulties have been avoided by replacing the whole erythrocyte cytosol either by a protein cofactor purified 1000-fold from this cytosol [18] or by an acetate or phosphate buffer used at high concentration [8].…”
Section: Resultssupporting
confidence: 67%
“…The ADP-ribosylation of G/F proteins in membranes from erythrocytes [5,6,10] (but apparently not from hepatocytes [20]) requires the presence of erythrocyte cytosol in addition to cholera toxin. In [4] we used the whole erythrocyte cytosol and cholera toxin to activate adenylate cyclase in pancreatic plasma membranes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cholera holotoxin molecule, a member of a family of bacterial heat-labile enterotoxins, is composed of a single A subunit (CT-A) and a pentamer of B subunits (CT-B) (Lospalluto and Finkelstein, 1972;Gill, 1976). The catalytic CT-A subunit disrupts regulation of ion channel function within the host intestinal epithelial cells causing inappropriate and substantial fluid efflux from the small intestine (Cassel and Pfeuffer, 1978;Gill and Meren, 1978). The CT-B pentamer required for secretion of the holotoxin outside the bacterial cell targets the CT-A subunit to the intestinal epithelium by interacting with host cell-surface GM 1 ganglioside (King and Van Heyningen, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both choleragen and LT require NAD for activation of adenylate cyclase in disrupted cells (9,11,12) and possess NAD glycohydrolase and ADPribosyltransferase activities (13)(14)(15). It has been proposed that both toxins exert their effects through the NAD-dependent ADP-ribosylation of either adenylate cyclase itself or of a protein critical to cyclase activation (9,11,(13)(14)(15)(16)(17). LT cross-reacts immunologically with antisera directed primarily against the B-subunits of choleragen (9,18,19).…”
Section: Introductionmentioning
confidence: 99%